International conflict and conservation of natural resources - Rolston, Holmes, 1932-2025, author; Wiley for Society for Conservation Biology, publisher (Colorado State University. Libraries, 1989)
Combined critical review of: Arthur H. Westing, ed., Cultural Norms, War and the Environment. Oxford and New York: Oxford University Press, 1988; Arthur H. Westing, ed., Environmental Warfare: A Technical, Legal and Policy Appraisal. London and Philadelphia: Taylor and Francis, 1984; Arthur H. Westing, ed., Herbicides in War: The Long-term Ecological and Human Consequences. London and Philadelphia: Taylor and Francis, 1984; Arthur H. Westing, ed., Explosive Remnants of War: Mitigating the Environmental Effects. London and Philadelphia: Taylor and Frances, 1985; Arthur H. Westing, ed., Global Resources and International Conflict: Environmental Factors in Strategic Policy and Action. Oxford and New York: Oxford University Press, 1986. Here are five remarkable and sobering volumes, with dozens of contributors, that explore in detail whether and how far there can be biological conservation in the face of war and international competition for resources. These studies are the work of the Stockholm International Peace Research Institute (SIPRI), financed by the Swedish Parliament, with an international staff. This series demonstrates beyond a shadow of a doubt that any one interested in biological conservation who fails also to take serious interest in political and social issues will soon fail in biological conservation.
Keywords: environmental policy; environmental warfare; pesticides; explosive remnants of war; global resources; cultural norms; future Earth